2022
DOI: 10.1007/s11357-022-00620-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota mitochondria disorders as hubs for early age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is a progressive neurodegenerative disease affecting the central area (macula lutea) of the retina. Research on the pathogenic mechanism of AMD showed complex cellular contribution governed by such risk factors as aging, genetic predisposition, diet, and lifestyle. Recent studies suggested that microbiota is a transducer and a modifier of risk factors for neurodegenerative diseases, and mitochondria may be one of the intracellular targets of microbial signaling molecules.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 249 publications
0
6
0
Order By: Relevance
“…In addition, previous studies have highlighted the essential role of mitochondria in the communication between the gut and brain [77,78]. The modulation of mitochondria, and especially a decrease in the activity of mitochondrial electron transfer complexes, is also associated with behavioral dysfunctions during aging [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have highlighted the essential role of mitochondria in the communication between the gut and brain [77,78]. The modulation of mitochondria, and especially a decrease in the activity of mitochondrial electron transfer complexes, is also associated with behavioral dysfunctions during aging [79,80].…”
Section: Discussionmentioning
confidence: 99%
“… 95 Recent research has shown that probiotics have a protective effect on mitochondria. 54 , 96 For instance, butyrate in cell lines derived from patients with autism has been found to regulate mitochondrial functions, including enhancing oxidative phosphorylation and β-oxidation under physiological stress or mitochondrial dysfunction 54 and activating the peroxisome proliferator-activated receptor-gamma coactivator-1alpha (PGC1α) signaling axis in NSC34-G93A cells to regulate mitochondrial biogenesis. 55 However, another study suggested that mitochondrial function and glutathione peroxidase 4 (GPX4)-dependent ferroptosis were boosted under the condition of supplementing butyrate.…”
Section: Intestinal Microorganisms Act On Ferroptosismentioning
confidence: 99%
“…The metabolic functions of nutrients are similar in both the microbiome and mitochondria. In addition, they have many structural and functional similarities and several proteins that regulate related or even the same metabolic processes (Fehér et al, 2022). According to recent findings, the microbiota interacts with the host cell, particularly by interacting with the mitochondria and microbial metabolites that also affect mitochondrial function and biogenesis (Zhu et al, 2022).…”
Section: Microbiota-mitochondria Inter-talkmentioning
confidence: 99%